2010
DOI: 10.1007/s13105-010-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to exercise in elite sportsmen during the competitive season

Abstract: Our aim was to evaluate the chronic effects of training and competition during a 4-month season on immune response in professional volleyball players. Players took part in an incremental maximal cycling test at the beginning and at the end of the season. As control group, subjects with regular recreational activity were selected. Blood samples were obtained at rest, immediately after the exercise test, and after 30 min recovery. Volleyball players have similar basal levels of erythrocytes, hematocrit, hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
8
45
1
2
Order By: Relevance
“…We did observe significant Polat 1439 increases of lymphocyte levels resulting from supplementation and exercise. In another study lymphocyte counts were elevated after hard exercise due to the acute phase inflammatory response it stimulated (Córdova et al, 2010). In another study, in spite of finding no changes in erythrocyte and leukocyte counts, zinc supplementation resulted in an increase of lymphocyte percentage in broiler chicks (Dönmez et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We did observe significant Polat 1439 increases of lymphocyte levels resulting from supplementation and exercise. In another study lymphocyte counts were elevated after hard exercise due to the acute phase inflammatory response it stimulated (Córdova et al, 2010). In another study, in spite of finding no changes in erythrocyte and leukocyte counts, zinc supplementation resulted in an increase of lymphocyte percentage in broiler chicks (Dönmez et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
“…Blood samples taken at rest before, during and after exhaustion were examined along with immune parameter analysis in volleyball players in a 4-month season. In that study, volleyball players had the same erythrocyte, hemoglobin and hematocrit values as the controls (Córdova et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Higher intensity and total volume as well as short rest intervals are associated with the magnitude of stress and muscle damage [2,9,19,23]. Numerous laboratory and field studies address changes in blood cortisol as response to different loads in different environments among athletes [1,3,4,6,8,10,16,18,21,23]. Recently Cunniffe and al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the informative content, frequent interventions have met limited practical application in competitive sport because of possible alteration in the regular course of the training cycle. Standardised repeated single interventions as longitudinal measures of hormonal, immunological and biochemical variables have been described in different sports, including team-game sports, as an expression of the impact of training [3,13,15,16,[18][19][20]23]. Analysis of longitudinal measurements can be carried out in comparison with an accepted reference interval but such an approach is not always productive in the case of athletes because of biological, procedural and environmental influences [12].…”
Section: Introductionmentioning
confidence: 99%
“…While moderate activity may enhance immune function over sedentary levels, excessive, prolonged and high-intensity exercise may impair immune function 28 . Some studies have shown that relatively short periods of intense training (1 to 3 weeks), may reduce the function of innate immune 29,30 . In our study, two weeks of high intensity exercise increased the phagocytic capacity and cationic vesicles content from neutrophils and macrophages in the training diabetics rats (Table 3-4)).…”
Section: Sementioning
confidence: 99%